Comprehensive Review of the Solubility Data of Glycine in Organic and Inorganic Phases at Various Temperatures - Sing, Nilam; Chakraborty, Jit; Roy, Sanjay (Recent Developments in Chemistry and Biochemistry Research Vol. 8, 2024)
Amino acids, including glycine, are fundamental to biochemical research due to their dual acidic and basic properties, allowing them to form peptides and proteins, the building blocks of life. The present review chiefly focuses on the solubility of glycine in a widespread temperature range as examined by several researchers worldwide. Glycine being the simplest amino acid has widespread application in several fields. Accordingly, it has been extensively studied, yet there is a lack of comprehensive reviews on its solubility data. In this review, the solubility data of glycine in pure water and in the presence of inorganic and organic electrolytes from 145 results across 45 published articles is compiled and presented. A simple linear model was applied to the reported solubility data, showing that glycine solubility increases by 0.0866 mol kg-1 per K. Based on this model, the solubility at 298.15 K was estimated to be 3.318 mol kg-1. This statistical approach provides more accurate solubility measurements, offering valuable insights for further studies. The study represented the solubility data of glycine at different temperature ranges by plotting the linear regression model to find the true solubility.